Conservation of aquatic invertebrates: concerns, challenges and conundrums - Collier, Kevin J.; Probert, P. Keith; Jeffries, Michael (Aquatic conservation, 2016)
Invertebrates inhabiting marine and freshwater ecosystems make important contributions to global biodiversity and provide significant services that have cascading effects across ecosystems. However, this group is grossly under‐represented in assessments of conservation status and often neglected in targeted aquatic conservation efforts. In global assessments of 7857 freshwater invertebrates and 2864 marine invertebrates, 30–34% were considered Data Deficient highlighting the paucity of information for making such assessments. Of the invertebrate groups that could be assessed, those with poor dispersal abilities and high local endemism, such as many gastropods, crayfish and mussels, are the most threatened. Springs and subterranean hydrological systems support the highest proportions of threatened freshwater species, while in marine environments coral reefs, lagoons and anchialine systems are particularly vulnerable. Key agents of biodiversity decline in aquatic ecosystems are water pollution, overexploitation and harvesting, habitat degradation and destruction, alien invasive species, and climate change. Effects of dams and water management along with pollution from urban, agricultural and forestry sources are the main threats in freshwater ecosystems, whereas a broad range of factors have impacts on marine invertebrates, including biological resource use. Significant impediments facing conservation of aquatic invertebrates are limited knowledge of their diversity, the need for broadscale actions to account for connectivity within and across ecosystems, lack of political will and investment, and the prospect that conditions may get worse before they improve, possibly not in time to save some already highly imperilled invertebrate species from extinction. Copyright © 2016 John Wiley & Sons, Ltd.